Pembangunan agroindustri dalam menggerakkan perekonomian - Unggul Priyadi (Universitas Islam Indonesia, 2000)
Economics crisis striking Indonesia nowadays should be treated seriously. Trying to recover the Indonesian economy, government has no choice other than strengthening the fundamental of the Indonesian economy.